1997
DOI: 10.1161/01.cir.96.9.2837
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Anti-Ischemic Effect of 17β-Estradiol in Postmenopausal Women With Coronary Artery Disease

Abstract: 17Beta-estradiol reduces the degree of pacing-induced myocardial ischemia in postmenopausal patients with coronary artery disease. The reduction of pacing-induced coronary sinus pH shift is consistent with an anti-ischemic effect of the hormone and is not due to preconditioning, as evidenced by the absence of improvement after placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
0
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 31 publications
3
13
0
4
Order By: Relevance
“…We observed effects of 17␤-estradiol within 5-15 min, suggesting an acute, nongenomic action. Clinical studies have demonstrated that such acute exposure to estrogen relieves myocardial ischemia (1,34) and increases coronary blood flow (33) in patients with established CAD and/or intimal dysfunction. Therefore, the present findings provide a molecular mechanism that can at least partially explain how estrogen enhances coronary blood flow via a NO-dependent, endothelium-independent mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed effects of 17␤-estradiol within 5-15 min, suggesting an acute, nongenomic action. Clinical studies have demonstrated that such acute exposure to estrogen relieves myocardial ischemia (1,34) and increases coronary blood flow (33) in patients with established CAD and/or intimal dysfunction. Therefore, the present findings provide a molecular mechanism that can at least partially explain how estrogen enhances coronary blood flow via a NO-dependent, endothelium-independent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This direct effect of estrogen on HCASMC may be an important mechanism for helping to counteract pathological coronary vasoconstriction in arteries with a damaged or diseased intima, as evidenced by clinical studies demonstrating that acute (15-30 min) administration of estrogen to postmenopausal women with CAD relieves myocardial ischemia (1,34) and increases coronary blood flow (33). At present, however, we know very little of how estrogen directly relaxes human CASM, especially in arteries with a dysfunctional endothelium.…”
mentioning
confidence: 99%
“…A large body of evidence suggests that estrogens inhibit the progression of atherosclerosis and have a important effects in the maintenance of arterial hemodynamics [2]. Short-term administration of 17β-estradiol has been shown to improve coronary and peripheral blood flow during exercise-induced myocardial ischemia in postmenopausal females with coronary artery disease [3,4]. These effects involve a number of mechanisms, including endothelium-derived nitric oxide production and release [5,6], and direct vascular smooth muscle relaxation by modulation of ion channels [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent evidence suggests that estrogen has direct effects on cardiac myocytes. These cardiovascular actions may contribute to the observations in population-based studies of a reduced risk of cardiovascular disease faced by premenopausal women compared with age-matched men, and of the increase in incidence of coronary artery disease after menopause.Estrogen has been observed to play a role in the pathogenesis of left ventricular hypertrophy [1][2][3]; attenuation of contractile function [4]; reduction of myocardial ischemic injury [5,6]; and the reduction of incidence of ventricular arrhythmias in experimental models of regional ischemia-reperfusion [7,8]. Estrogen is classically understood to act via its steroid receptor, chiefly in the nucleus.…”
mentioning
confidence: 99%
“…Estrogen has been observed to play a role in the pathogenesis of left ventricular hypertrophy [1][2][3]; attenuation of contractile function [4]; reduction of myocardial ischemic injury [5,6]; and the reduction of incidence of ventricular arrhythmias in experimental models of regional ischemia-reperfusion [7,8]. Estrogen is classically understood to act via its steroid receptor, chiefly in the nucleus.…”
mentioning
confidence: 99%